Accès et admission à l'enseignement supérieur : contraintes globales, réponses locales ? - Gaële Goastellec (Les éditions de la Maison des sciences de l'Homme, 2006)
This article examines higher education access systems and policies, with illustrations from field research carried out in American and Indonesian universities. Three global pressures are impacting on access: The demographic pressure comes first. It is at the congruence of a mechanical increase in the population, a political choice to widen access, a bigger social demand and a growing symbolic pressure embedded in the concept of knowledge based economy. This demographic pressure carries within itself the two others pressures: The economic pressure, with the diffusion of the concept of efficiency, and the political pressure, that calls for diversification of the student body, especially when it comes to the selection of an elite. Through the analysis of these three pressures, this article highlights the international circulation of some issues within higher education spheres and intends to show how specific local responses can themselves take part in this convergence process.